GlucoTRIG: a novel tool to determine the nutritional quality of foods and meals in general population - Rohith N. Thota; Paul J. Moughan; Harjinder Singh; Manohar L. Garg (Lipids in Health and Disease, 2020)
Abstract Background This study aimed to develop a novel criterion, GlucoTRIG, to rank meals for healthiness, that considers both glycaemic (serum insulin) and lipaemic (serum triglycerides) responses. Methods Healthy volunteers (n = 10) were recruited with the aim of deriving a standard GlucoTRIG value for a reference meal. Volunteers consumed the reference meal (2 regular slices of wholemeal bread; 250 mL chocolate flavoured milk; 7 g butter and 11 g peanut butter) comprising of carbohydrate, fat and protein (41, 40 and 16% energy respectively) on three different occasions with a minimum washout period of 3 days. The GlucoTRIG value was determined as the difference between the product of insulin and triglyceride obtained from venous blood samples at baseline and the product of insulin and triglyceride at 180 min. Results There were no significant differences in the participants’ dietary intakes and their metabolic parameters between three visits (P > 0.005). The GlucoTRIG value obtained from three mean values of the reference meal was found to be 19 ± 3.5. There were no significant (P = 0.2303) differences observed between the GlucoTRIG values for the three visits. Conclusion GlucoTRIG, consisting of both glycaemic and lipaemic responses, may be a physiologically relevant tool to rank foods and meals for reducing the risk of metabolic diseases. Trial registration ACTRN12619000973112 .